(untitled) (Development Service Industry Management, 2024)
The article examines the process of assessing the development of human resources in enterprises in the face of modern economic challenges and analyzes modern approaches to assessing human resources, taking into account both quantitative and qualitative characteristics of personnel. Particular attention is paid to determining the criteria for the effectiveness of human resources, methods for its development and adaptation to changing economic conditions. It is determined that in conditions of uncertainty and global changes, human resources become one of the key competitive advantages of an enterprise, and an effective assessment system allows ensuring the sustainable development of the organization. In the process of analysis, the advantages and disadvantages of various approaches are considered, as well as possible development trends in the conditions of globalization and digitalization of the economy. Therefore, in the conditions of constant changes in the labor market, modern approaches should be more flexible, oriented to long-term planning, and also include elements of adaptation to rapidly changing conditions and key factors to ensure high performance and sustainable development of the organization in the conditions of the modern business environment. Human resources management is one of the key components of the effective functioning of any enterprise. Modern organizations operating in a dynamic and competitive environment must take into account not only the technical and financial aspects of their activities, but also the effectiveness of the use of human capital. The assessment of the personnel potential of the enterprise becomes an important tool in ensuring its development, as it allows you to identify the strengths and weaknesses of the existing personnel, optimize the processes of selection, training and development of employees, as well as contribute to the achievement of the strategic goals of the organization. The importance of personnel potential for the organization is that the ability of the enterprise to function effectively and achieve competitive advantages in the market depends on the qualification, professionalism, motivation and adaptation of employees. In this context, the assessment of personnel potential allows to identify existing problems in personnel management, to respond in a timely manner to changes in the external environment, as well as to determine directions for improving the efficiency of the work of each employee and the organization as a whole.